2021
DOI: 10.17582/journal.aavs/2021/9.10.1608.1615
|View full text |Cite
|
Sign up to set email alerts
|

Intake, Nutrient Digestibility and Production Performance of Pesisir Cattle Fed Tithonia diversifolia and Calliandra calothyrsus-Based Rations with Different Protein and Energy Ratios

Abstract: The productivity of Pesisir cattle is influenced by the protein-energy ratio in the feed. The purpose of this study was to determine the ratio of crude protein (CP) and total digestible nutrients (TDN) inefficient feed for production in Pesisir cattle, by looking at intake, nutrient digestibility, and production performance. Four male Pesisir cattle with an average initial body weight of 118.13 ± 13.13 kg, were designed with a latin square design into 4 feed treatments: treatment T1 (CP 14.45% and TDN 57.53%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 0 publications
6
26
0
Order By: Relevance
“…By subtracting the number of rations delivered from the remaining rations, the ration intake was calculated. These formulas were used to determine nutrient intake of ECDG (Pazla et al 2021a). Dry matter intake = dry matter of rationdry matter residual of ration Organic matter intake = dry matter intake x organic matter of ration Crude protein intake = dry matter intake x crude protein of ration…”
Section: Variables Analysis Nutrient Intakementioning
confidence: 99%
See 1 more Smart Citation
“…By subtracting the number of rations delivered from the remaining rations, the ration intake was calculated. These formulas were used to determine nutrient intake of ECDG (Pazla et al 2021a). Dry matter intake = dry matter of rationdry matter residual of ration Organic matter intake = dry matter intake x organic matter of ration Crude protein intake = dry matter intake x crude protein of ration…”
Section: Variables Analysis Nutrient Intakementioning
confidence: 99%
“…It is critical to determine the animal's amount of consumption in order to calculate the nutrients available for maintenance and production (Barreto et al 2012). High level of consumption affects livestock production performance (Pazla et al 2021a;Saldanha et al 2021). Furthermore, according to Baumont (1996), palatability of the feed is defined as all the physical (plant bearing, spines, etc.)…”
Section: Nutrient Intakementioning
confidence: 99%
“…Forage feeding greatly affects milk fat content [8]. Forage eaten by livestock undergoes a fermentative process in the rumen by rumen microbes [9], [10]. The main product of fermentation in the rumen is VFA (Volatile fatty acids) [11], [12].…”
Section: Resultsmentioning
confidence: 99%
“…Phytic acid causes a bitter taste, so it can reduce feed consumption if the dose is excessive. Pazla et al (2021b) reported a decrease in ration consumption in Pesisir cattle with a 30% tithonia level in the diet.…”
Section: Methodsmentioning
confidence: 99%
“…Tithonia contains antinutritional substances such as flavonoids, tannins, alkaloids, phytic acid, saponins, and oxalate (Aye, 2016). Phytic acid is an antinutrient with the highest amount, 79.2 mg/100 g, and can reduce the palatability of livestock (Oluwasola and Dairo, 2016;Pazla et al, 2021b). One of the processing methods that can reduce phytic acid in Tithonia is fermentation.…”
mentioning
confidence: 99%